Two-dimensional metal-organic framework materials for energy conversion and storage - Tang, Xuxu; Zhao, Lu; Sun, Weiwei; Wang, Yong (Journal of power sources, 2020)
Selecting and assembling metal ions and bridging ligands can fabricate two-dimensional metal-organic framework nanosheets, which can act as prospective materials for efficient energy applications. Thanks to large surface area and more porosity, ultrathin 2D MOFs nanosheets and their derived two-dimensional nanosheet materials exhibit more highly approachable active sites uncovered on the surface, decreased ion diffusion distance and fast electron transfer for energy storage/conversion applications. Herein, this review will summarize the latest developments with discussion of design, fabrication, energy storage as well as conversion performance of 2D MOFs and their-derived two-dimensional materials. Moreover, the development of exfoliated two-dimensional MOFs and their derivatives, as well as the promising trends and prospects in application as excellent-performance electrode materials in batteries, supercapacitors, and electrocatalysis are also present. [Display omitted] •Recent developments of 2D MOF materials for energy applications are reviewed.•Design strategies of 2D MOF related materials are summarized.•Relationship between the structure and performance is discussed in details.•Future research tendency of 2D MOF-related materials is highlighted.